Design of low profile end-fire surface wave antenna - Yang, Shuo (2016)
The dissertation project involves the design and simulation of a low profile end fire surface wave antenna that operates at UHF band. Our proposed surface wave antenna consists of three parts, which are the probe-fed unidirectional surface wave launcher, the tapered surface wave radiation structure and the tapering connection structure linked in between. In the surface wave launcher, a vertical reflecting wall of rounded rectangle and a metallic ridge are utilized to transform the cylindrical waves excited by the coaxial probe to surface waves, which can improve the efficiency of the surface wave excitation and the operating bandwidth. The tapered grounded surface wave radiation slab which is made up of ceramic with high permittivity will radiate the surface waves transferred from the surface wave launcher into free space. The connection part with tapering height in between is to reduce the abrupt influence of the great difference of permittivity between the surface wave launcher and the surface wave radiation structure, which will decrease the transmission loss and increase the radiation efficiency. The low profile end fire surface wave antenna with bandwidth of 20% and low profile of (1/30) h> operates at the center frequency of 500 MHz and can be mounted on the surface of the airborne applications such as unmanned aerial vehicles (UAVs).